Soil Organic Matter, Mitigation of and Adaptation to Climate Change in Cocoa–Based Agroforestry Systems - Gusli, S.; Sumeni, S.; Sabodin, R.; Muqfi, I.H.; Nur, M.; Hairiah, K.; Useng, D.; Noordwijk, M. van (MDPI, 2020)
Belowground roles of agroforestry in climate change mitigation (C storage) and adaptation (reduced vulnerability to drought) are less obvious than easy-to-measure aspects aboveground. Documentation on these roles is lacking. We quantified the organic C concentration (Corg) and soil physical properties in a mountainous landscape in Sulawesi (Indonesia) for five land cover types: secondary forest (SF), multistrata cocoa–based agroforestry (CAF) aged 4–5 years (CAF4), 10–12 years (CAF10), 17–34 years (CAF17), and multistrata (mixed fruit and timber) agroforest (MAF45) aged 45–68 years. With four replicate plots per cover type, we measured five pools of C-stock according to IPCC guidelines, soil bulk density (BD), macro porosity (MP), hydraulic conductivity (Ks), and available water capacity of the soil (AWC). The highest C-stock, in SF, was around 320 Mg ha−1, the lowest, 74 Mg ha−1, was in CAF4, with the older agroforestry systems being intermediate with 120 to 150 Mg ha−1. Soil compaction after forest conversion led to increased BD and reduced MP, Ks, and AWC. Older agroforestry partly recovered buffering: AWC per m of rooted soil profile increased by 5.7 mm per unit (g kg−1) increase of Corg. The restored AWC can support about a week’s worth of evapotranspiration without rain, assisting in climate change adaptation.